Deteksi kavitasi menggunakan linear discriminant analysis pada pompa sentrifugal - Berli Paripurna Kamiel; Yusuf Ahmad; Krisdiyanto Krisdiyanto (TURBO [Tulisan Riset Berbasis Online], 2020)
Cavitation is a phenomenon that often occurs in the centrifugal pumps. The impact of cavitation is a decrease in pump performance which will affect the ongoing production process in the industries. It is important to have a method to detect the phenomenon of cavitation early. The vibration signal is a parameter that is often used in detecting cavitation or other faulty components. One of the methods is based on the pattern recognition i.e. machine learning. Linear Discriminant Analysis (LDA) is a machine learning algorithm that has the advantage of reducing the parameters used into low dimensions without reducing the accuracy of their classification. The study proposes LDA to classify normal conditions, initial cavitation, intermediate cavitation and severe cavitation. The recording of the vibration signal is taken using the an accelerometer mounted on the inlet of the centrifugal pump. The vibration signal is then extracted using 10 statistic parameters of time domain as the LDA feature selection, namely mean, RMS, standard deviation, kurtosis, skewness, crest factor, clearance factor, shape factor, variance and peak value. The results shows that the LDA classifier can detect and classify cavitation conditions with an accuracy rate of 98.8% on training and 99.6% on testing. The shape factor, kurtosis, skewness and RMS parameters are a combination of parameters that have a large contribution to the classifier to detect and classify cavitation conditions.Keywords: Linear Discriminant Analysis (LDA), cavitation, centrifugal pump, statistical parameter